Amorphous‐Ga2O3 Optoelectronic Synapses with Ultra‐low Energy Consumption. (17th October 2021) - Zhu, Rui; Liang, Huili; Hu, Sigui; Wang, Yan; Mei, Zengxia
Abstract: Developing optoelectronic synaptic devices with low energy consumption is of critical importance for neuromorphic computing and visualization systems. In this work, amorphous‐Ga2 O3 (a‐Ga2 O3 ) is adopted to realize a low‐power optoelectronic synapse considering its distinguished features of ultra‐wide bandgap, high responsiveness to light stimulation, and strong persistent photoconductivity effect. The basic synaptic functions such as short‐term plasticity (STP) and long‐term plasticity (LTP) have been successfully mimicked. A noise suppression capability is achieved as well, similar to the visual cells. Strikingly, the total energy consumption for triggering an LTP synaptic event is only 136 fJ, approaching the one of a biological synapse. The underlying mechanism for the a‐Ga2 O3 synaptic performance is explored with a combined research of X‐ray photoelectron spectroscopy, Kelvin probe force microscopy, electric tests, and Technology Computer‐Aided Design simulations. The consistent results suggest the key role of the synergetic modulation effect of optical and electric fields on the dynamic behaviors of oxygen vacancy (VO ) defects. This work indicates the potential applications of a‐Ga2 O3 in low‐power optoelectronic synapses. Abstract : Amorphous Ga2 O3 is applied to compose the optoelectronic synapse with low energy consumption. The short‐term plasticity (STP) and long‐term plasticity (LTP) functions have been successfully mimicked. A noise suppression capability is achieved as well. Strikingly, the total energy consumption for triggering an LTP synaptic event is only 136 fJ.